Comparison of the Lytic Blood Culture Method with the Conventional Blood Culture Method in Cases of Enteric Fever in a Tertiary Care Hospital (Bangladesh Journal of Infectious Diseases, 2017)
Background: Blood Culture is the gold standard and accurate method of diagnosing bacteremia in enteric fever; however, conventional blood culture is slow in isolating Salmonella typhi and Salmonella paratyphi.Objective: The main aim of this study was to compare the result of the lytic centrifugation method with conventional blood culture system for the accurate diagnosis of enteric fever in febrile patients.Methodology: The cross-sectional study was carried out in the department of Microbiology, Mymensingh Medical College, Mymensingh between July 2010 and June 2011 including 200 individuals of different ages and sexes. Of them, 150 were clinically suspected cases of typhoid fever and 50 controls comprising of 25 non-typhoidal febrile patients and 25 healthy individuals. Both types of blood culture were performed for each of the cases and controls.Result: The lytic centrifugation method recovered more organisms (17.3%) than the conventional blood culture method (13.3%). Time required for isolation of S. typhi and S. paratyphi A was short in lytic method (18-20hours) than conventional method (42-72hours). Total contamination rate was 0.5% by lytic as compared to the conventional blood culture method which was 5.0%.Conclusion: In conclusion the lytic method is better than conventional blood culture system for good result, short isolation time and less chance of contamination.Bangladesh Journal of Infectious Diseases 2016;3(1):6-10